(untitled) (Research, Society and Development, 2022)
The aim of the study was to evaluate and correlate the angular measurements of the hip, knee and foot with medial displacement of the femur in the frontal plane in male professional soccer players. It was a cross-sectional observational study including twenty-nine professional soccer players recruited from a soccer team who participated in the preseason evaluation, with mean age 22 years (± 4.36), Body Mass 73.74 (± 9.88) kg and Height 179.00 (± 0.09) cm. Angular measurements were collected on both lower limbs of Active Forefoot Alignment, Active Ankle Dorsiflexion Movement Range, Passive Medial Hip Rotation, Body Mass Index, and frontal alignment of the knee and hip through the Step Down Test. For the right lower limb, there was no significant correlation for the variables analyzed in relation to medial deviation of the femur. The same happens with the lower left limb in relation to the medial deviation of the femur. When the relationship of the variables between the two limbs was evaluated, a significant value was observed for medial displacement of the femur (r = 0.694); as well as for ankle dorsiflexion (r = 0.841) and medial hip rotation (r = 0.477). For forefoot alignment, there were no significant values ​​between the sides (0.389). It is concluded that there is no relation between the angular measurements of active ankle dorsiflexion, active forefoot alignment, passive medial hip rotation and body mass index with femoral medial deviation in professional soccer players.